Pembentukan Mutan Hipovirulen Fusarium oxysporum f.sp cubense Penyebab Layu pada Tanaman Pisang (Musa paradisiaca L.) Menggunakan Asam Nitrat - Fransen Sinaga; Made Sritamin; I Ketut Suada (Nandur, 2021)
The Formation of Fusarium oxysporum f.sp. cubense Hypovirulent Mutant Causes Wilt in Banana Plants (Musa Paradisiaca L.) Using Nitric Acid. Fusarium wilt disease is a type of disease that can cause a quantitative decrease in banana plant production. Fusarium wilt disease is classified as a disease that is difficult to control, because it is underground and forms chlamydospores. Control of Fusarium with biological agents has a positive impact on the environment, one way of biological control using antagonistic microorganisms. Biological agents used are biological agents that are hypovirulent. Hypovirulent properties will compete with host pathogens in competition for space, food, and toxin excretion, thereby suppressing fusarium fungi to enter the vascular tissue of banana plants. Chemical mutagens are mutagenic agents that can cause permanent changes in the composition of DNA. Nitric acid can cause DNA cross-linking in the same strands. Nitric acid was reported as a suitable mutagen to increase the production of lactic acid Lactobacillus delbrueckii. Nitric acid can change the acid-base pair of organisms so that mutations occur. obtained a mutant that is hypovirulent which can suppress the growth of fusarium fungus as a pathogen in banana plants. The results showed that the FOC fungus isolates with 1% treatment had hypovirulent properties compared to 0.05%, 0.1% and 0.5% treatments. Hypovirulent properties are derived from the timing of symptoms. In mutant FOC, 1% of symptoms appeared on day 6. The growth of hypovirulent mutants was expected to be higher than that of pathogenic FOCs. Based on the research, it was found that the fungi had the lowest pathogenicity level, as well as high diameter growth, total spore density, and high amount of inhibition.